2019
DOI: 10.1093/cvr/cvz202
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting blood pressure lowering effects of nitrite are NO-independent and mediated by hydrogen peroxide, persulfides, and oxidation of protein kinase G1α redox signalling

Abstract: Aims Under hypoxic conditions, nitrite (NO2−) can be reduced to nitric oxide (NO) eliciting vasorelaxation. However, nitrite also exerts vasorelaxant effects of potential therapeutic relevance under normal physiological conditions via undetermined mechanisms. We, therefore, sought to investigate the mechanism(s) by which nitrite regulates the vascular system in normoxia and, specifically, whether the biological effects are a result of NO generation (as in hypoxia) or mediated via alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In fact, this response was also found with nitrate administration and significantly attenuated by the use of oral mouthwash, which impaired the enterosalivary cycle of nitrate and prevented nitrate from being reduced to nitrite, thus reducing the increases in circulating S-nitrosothiols and vascular protein nitrosylation [ 3 , 10 , 11 ]. Several recent studies by other groups have described vascular effects of nitrite that are not necessarily associated with increased NO production [ [27] , [28] , [29] ], thus strongly suggesting the involvement of other pathways such as catalase inhibition [ 28 ] or increased S-nitrosylation 26 as possible mechanisms activated by nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this response was also found with nitrate administration and significantly attenuated by the use of oral mouthwash, which impaired the enterosalivary cycle of nitrate and prevented nitrate from being reduced to nitrite, thus reducing the increases in circulating S-nitrosothiols and vascular protein nitrosylation [ 3 , 10 , 11 ]. Several recent studies by other groups have described vascular effects of nitrite that are not necessarily associated with increased NO production [ [27] , [28] , [29] ], thus strongly suggesting the involvement of other pathways such as catalase inhibition [ 28 ] or increased S-nitrosylation 26 as possible mechanisms activated by nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…In the endothelium, H 2 O 2 acts as a vasodilator and has been considered to be an endotheliumderived relaxing factor, effects that are induced largely through activation of PKG1a and posttranslational modifications involving S-glutathionylation. 47,48 Increased intracellular H 2 O 2 promotes phosphorylation of p66Shc, a key mitochondrial ROS regulator that involves vascular endothelial growth factor, which is important in endothelial cell migration, proliferation, and angiogenesis. 49 In vascular smooth muscle cells, we demonstrated that H 2 O 2 induces posttranslational modification of ERK1/2 and p38MAPK through tyrosine kinaseedependent, protein kinase C (PKC)eindependent mechanisms, processes that are up-regulated in hypertension.…”
Section: R Esum Ementioning
confidence: 99%
“…2012; Feelisch et al . 2019). To our knowledge, the metabolic fate of NO and NOx has not been studied in the placenta.…”
Section: Introductionmentioning
confidence: 99%